Impact of the factors of animal production and welfare on robotic milking frequency - Córdova, Helder de Arruda; Alessio, Dileta Regina Moro; Cardozo, Leonardo Leite; Thaler Neto, André (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the impact of production factors on milking frequency and the latter’s effect on animal welfare in robotic milking. The experiment was performed with Holstein Friesian cows housed in free-stall barns. To assess the impact of production factors, body condition score, milk yield, and concentrate intake were determined. To determine the effects of the milking frequency on welfare, the locomotion and teat-end scores and serum cortisol level were evaluated. Three experimental groups were formed according to the daily average milking frequency: 1.0 to 1.9, 2.1 to 2.9, and above 3.0 milkings per day. The decrease in milking frequency during lactation was related to the reduction in concentrate intake and milk yield. The increase in milking frequency was related to the reduction in the milk flow and the increase in milking duration. Milking frequency was affected by concentrate intake, locomotion problems, milk yield, and lactation stage. The cortisol level and teat-end conditions were not affected by milking frequency. Milking frequency impacts milk flow, duration of milking, and milk composition; however, there is no effect on the indicators of animal welfare.
Keywords: cortisol; free-stall system; lactation; milk yield; voluntary milking system